(untitled) (Studia Prawnicze / The Legal Studies, 1981)
In contemporary systems of taxation property taxes appear as: 1) substitute and supplementation of other types of taxes imposed on objects free from them; 2) instrument of discrimination of certain phenomena already levied with other taxes; 3) instrument of taking over a part of property belonging to a taxpayer. Each of the above uses of property taxes may serve realization of fiscal and other than fiscal tasks (e.g. economic, social). The purpose of this article is to answer a following question: are property taxes used in nowadays social and economic conditions in Poland justified and if so, what tasks should these types of taxes fulfil? The analysis of property taxes levied on property, its acquisition, loss or accruer, allows to formulate a thesis that evolution of principles and structure of taxation of property in Poland is aimed at making use of property taxes first of all to carry out tasks of fiscal character. In the light of changes occuring on present stage of social and economic development, making use of property taxes in order to carry out fiscal tasks seems to be unjustified. Property taxes should be levied only on such property, the taxation of which is socially fully justified. In particular property taxes should ensure: 1) elimination of certain socially negative phenomena consisting in enlarging property by way of speculation concerning material goods, 2) correction of the size of property significantly surpassing average size.